The relationship between ADHD symptoms and driving behavior in college students: The mediating effects of negative emotions and emotion control. (April 2015) - Oliver, Michele L.; Han, Kyunghee; Bos, Alexander J.; Backs, Richard W.
Highlights: Examined ADHD symptoms, negative emotion, emotion control, and driving behavior relationship. Examined mediating effects of negative emotions and emotion control on driving anger and safe driving behavior. Negative emotions and emotion control were found to be significant mediators on driving anger. Results are important for designing driving safety training programs for people with ADHD symptoms. Abstract: Previous research has shown a relationship between attention deficit-hyperactivity disorder (ADHD) symptoms and driving anger and adverse driving outcomes. Moreover, adults with ADHD symptoms express their emotions in more aggressive ways, indicating a lack of emotion control. The present study surveyed 246 college students to examine the relationship among ADHD symptoms, negative emotions, emotion control, and driving anger and safe driving behavior. Mediating effects of negative emotions and emotional control on the relationship between ADHD symptoms and self-reported driving anger and safe driving behavior were also examined. Both negative emotions and emotion control were significant mediators of the relationship between ADHD symptoms and driving anger, but not safe driving behavior. Mediation was stronger for ADHD-Hyperactive/Impulsive symptoms than for ADHD-Inattention symptoms. These results may provide some insight on how to design training programs for individuals with ADHD symptoms to increase driving safety.